A SURVEY OF VOCABULARY USED IN ONLINE FOOD RECIPE WEBSITES - Bunsaeng, Sommai; Dennis, Nutprapha K. (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this study was to survey vocabulary used in online Thai food recipes from two websites www.BBCGoodFood.com and www.ThaiTable.com. The ten selected recipes analyzed in this study were only from the Thai main course recipes category. The vocabulary used is categorized into 8 categories as parts of speech; noun, pronoun, verb, adverb, adjective, preposition, conjunction, and determiner. The results of the study showed that there were 1,468 words with 8 types of parts of speech. The results revealed that in the ten recipes it used nouns the most with 372 words (37.2%) and least is pronoun with 10 words (0.7%). Results of the study showed that learners can study many different kinds of words. The learner can analyze the function and kind of the word that is in the instruction; the base form of part of speech is helpful for making instruction in the recipe writing.